Otros orígenes del universo: Una estrategia de pedagogía decolonial para el desarrollo del pensamiento crítico en niños de grado sexto de la I.E.D. Paulo Freire (2022)
This didactic proposal seeks to develop and enhance critical thinking in sixth grade children through a printed material in the form of a primer or educational text, having as a central focus, different worldviews about the origin of the universe presented and created by native peoples from different parts of the world such as: the Viking Dublin people, the American Inga people, the African Zulu people and the Chinese Leiyang people. Thus, allowing to rescue and make visible those ancestral and popular knowledge, opposing to that Eurocentric logic, which frames all fields of knowledge in the school.